(untitled) (Research, Society and Development, 2022)
Cancer treatment results in considerable adverse effects, with oral mucositis being the most reported complication. This study aimed to compare the effect of three mouthwashes formulated from herbal medicines in the prevention and therapy of oral lesions caused by mucositis. Patients who were undergoing chemotherapy treatment at the Santa Terezinha de Joaçaba/SC University Hospital were used as a sample. After approaching the interviewees, a free and informed consent form was signed, followed by an interview to collect information related to the patient and his current cancer-related condition. Patients were divided into 03 groups with 11 participants, each group receiving one of the three solutions studied. The participants were then instructed to rinse their mouths with 10ml of the solution, 04 times a day for 05 days. After the application, information was collected through telephone calls, based on the Oral Mucositis and Daily Questionnaire. As for the pain reported by the patients, 22 (71%) answered "no pain" and 17 (55%) rated their pain, on a scale from 0 to 10, with a score of 1. Only 1 patient (3%) answered "a lot of pain", classifying it as a score of 9. Regarding the reported limitations, 22 (71%) had no limitations in eating and speaking. Only 1 (3%) reported difficulty speaking and "very limited" in drinking and eating. No patient reported disability. It was concluded that the herbal solutions used as a therapeutic form showed similar effectiveness. However, no patient developed mucositis during the period of mouthwash use, suggesting an effect also as a preventive factor.